Brief Version of Caffeine Expectancy Questionnaire in Brazil - Mendes, Guilherme Falcão; Reis, Caio Eduardo Gonçalves; Nakano, Eduardo Yoshio; Zandonadi, Renata Puppin (Frontiers in Nutrition, 2021)
Extensive questionnaires’ application has the limitation of filling time bias, related to the ability to focus and accurately respond to many items, justifying the necessity for a brief version. This study aimed to build a brief version of the Caffeine Expectancy Questionnaire – Brazil (B-CaffEQ-BR) composed of 21 items divided into 7 factors, with adequate consistency and reproducibility as the full version. Quantitative procedures using statistical modeling were applied using the CaffEQ-BR (full version) database keeping the Mean Absolute Error (based on the full version) less than 0.5 and Cronbach's alpha and Intraclass Correlation Coefficient – ICC ≥ 0.7. The expert panel (n = 3), in a blind design, evaluated the semantic structuring within the options indicated by previous statistical modeling until the expert panel's agreement. The participants (n = 62), Brazilian adults regular caffeine consumers (175.8 ± 94.4 mg/day), 62.9% women, 33.1 ± 9.7 y, 24.5 ± 3.8 kg/m², 62.9% self-identified as white, were asked to respond twice the online questionnaire in an interval of 48 – 72 hours. The first sample (n = 40) tested interobserver reproducibility with the twice application of B-CaffEQ-BR. Another sample (n = 22) answered the CaffEQ-BR (full version) and B-CaffEQ-BR, and the last sample (n = 18) performed the reverse process. The B-CaffEQ-BR presented excellent internal consistency (Cronbach’s alpha ≥ 0.729) and overall reproducibility (ICC ≥ 0.915) for the entire questionnaire and its seven factors. The B-CaffEQ-BR can be a valuable tool in caffeine research with the Brazilian adult population.